Sustainability in Palm Waste Management: Land Application Systems in a Quadruple Bottom Line Perspective - Kawile, Tirza Fitriani; Jurana; Zahra, Femilia; Mustamin (Equivalent : Journal of Economic, Accounting and Management, 2025)
The study focuses on the description of the implementation of the land application system on the sustainability of palm oil liquid waste management. The application of qualitative descriptive methods is the method used to analyze data obtained from interviews, observations and documentation. The results of the study indicate that the Land Application System is the Company's Driving Wheel in Carrying Out Sustainability in Palm Oil Liquid Waste Processing, the Quadruple Bottom Line Perspective coherently explains Processing activities starting from the Economic Perspective in Efficient Budget, the Environmental Perspective explains the Company's Concern in Minimizing environmental effects, the Social Perspective supports the empowerment of the surrounding Community, and the Governance Perspective ensures the implementation of operational standards based on government policies and encourages companies to move towards sustainability.